Qualitative analysis for the improvement of the Historic Sanctuary of Machu Picchu - Arriola Miranda, Angélica María (2020)
The Historic Sanctuary of Machu Picchu, an element of the tangible historical heritage of Peru, declared a World Heritage Site by Unesco, is undoubtedly one of the main tourist attractions in South America; which supports high tourist pressure, saturation problems and risk of impact on its conservation. In the present work, an audit of the level of quality in the tourist management of the site is carried out using the Delphi method. The vision of two types of specialists is obtained: academic and professional, in the tourism sector, on measures to mitigate the situation described and thus propose guidelines that aim to improve tourism competitiveness. The points of view and proposals of university researchers and managers of tourism companies is relevant in relation to the future of the Historic Sanctuary of Machu Picchu. The conclusions of the research, depending on the originality of its objectives and methodology, are of interest for the management of this world heritage site.